Foliar Application of Bread Yeast and Organic Fertilizer to Improve Vegetative Characters of Thompson Seedless Grape Vine (Vitis vinifera L.) - Al-Hawezy, Shabaq Muhammad Nafea; Ibrahim, Chnar Ali (Sulaimani Journal for Pure and Applied Sciences, 2018)
The study was conducted during growing season (2015) in a vineyard at Erbil Directorate of Agriculture Researches / Kurdistan Region / Iraq to investigate the possible effects of foliar application of (bio-fertilizer) natural bread yeast (0, 4, 8 and 12g.l-1) and (B&S Pot-min) liquid organic fertilizer (0, 2 and 4ml.l-1) on vegetative growth of (11) years old grapevine cultivar (Vitis vinifera L.) cv. Thompson seedless. Results indicated that the concentration of 12 g.l-1 of bread yeast increased leaf area and leaf length significantly over other concentrations of bread yeast. Moreover, liquid organic fertilizer at 4ml.l-1 caused significant increase in leaf area and leaf length over other concentrations. Interaction between 12g.l-1 bread yeast with 4ml.l-1 liquid organic fertilizer pointed significant surpass in leaf area and leaf length over other interactions.
Keywords: Bread yeast; Liquid organic fertilizer; grapevine; Thompson seedless; Vegetative growth